2010
DOI: 10.3109/01612840.2010.490929
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Treatment Fearfulness and Help-Seeking

Abstract: A majority of people meeting the criteria for mental disorders underutilize mental health services. Treatment fearfulness is a barrier to help-seeking. This study explores the way treatment fearfulness affects the help-seeking behaviour of individuals who sought help from the Community Mental Health Centre. A total of 290 participants completed a structured questionnaire. Information was obtained on a number of variables, including orientation toward utilization of social networks, attitudes toward seeking pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Our findings are also in concordance with the findings of Becker and colleagues [Becker, 1974;Janz and Becker, 1984]. Second, similar to other studies, we found that emotions, such as fear, stress, and angriness, motivate information seeking [Stoeckle et al, 1963;Borgers et al, 1993;Zartaloudi and Madianos, 2010]. Likewise, Zola [1973] found that the perceived interference with work or physical activity (i.e., costs) is one of the five important non-physical triggers for seeking medical aid.…”
Section: Osh Questions and Seeking Informationsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are also in concordance with the findings of Becker and colleagues [Becker, 1974;Janz and Becker, 1984]. Second, similar to other studies, we found that emotions, such as fear, stress, and angriness, motivate information seeking [Stoeckle et al, 1963;Borgers et al, 1993;Zartaloudi and Madianos, 2010]. Likewise, Zola [1973] found that the perceived interference with work or physical activity (i.e., costs) is one of the five important non-physical triggers for seeking medical aid.…”
Section: Osh Questions and Seeking Informationsupporting
confidence: 92%
“…Likewise, Zola [1973] found that the perceived interference with work or physical activity (i.e., costs) is one of the five important non-physical triggers for seeking medical aid. Second, similar to other studies, we found that emotions, such as fear, stress, and angriness, motivate information seeking [Stoeckle et al, 1963;Borgers et al, 1993;Zartaloudi and Madianos, 2010]. Third, comparable to the Attitude, Social Influence and (self) Efficacy (ASE) Model [de Vries et al, 2006] ''social influence,'' or in our study ''encouragement by the social environment to solve the question,'' can motivate information seeking.…”
Section: Osh Questions and Seeking Informationsupporting
confidence: 88%
“…Unmet needs for mental health care are well documented and psychosocial reasons are significant for not seeking needed mental care. There is evidence that access to mental health care is limited due to stigma and discrimination [30] or the fear of treatment [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite these apparent benefits, individual willingness to seek help from both personal and professional sources is often quite low (Zartaloudi and Madianos 2010). Individual factors associated with reduced help-seeking include the perceived need for self-reliance (i.e.…”
Section: Social Support and Help-seekingmentioning
confidence: 99%